PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS OF ENHANCING FUTURE TEACHERS’ PRACTICAL READINESS FOR COLLABORATIVE LEARNING - Karshieva Shakhnoza Valiyevna (Modern World Education: New Age Problems – New solutions, 2025)
The article examines the psychological and pedagogical foundations of forming future teachers’ practical readiness for organizing and implementing collaborative learning in school practice. The author presents a structural-functional model of readiness that integrates motivational-volitional, cognitive-operational, communicative-cooperative and reflective-evaluative components. The results of a three-year (2022–2025) experimental study conducted at Kokand State University involving 214 undergraduate students are presented. It has been established that systematic inclusion of students in real and simulated collaborative practices using digital tools (Microsoft Teams, Miro, Padlet, Mentimeter) and specially designed training projects significantly increases all components of readiness (p < 0.001, Cohen’s d = 1.68–2.44). Practical recommendations are given for the integration of the developed technology into the curricula of pedagogical universities.